The formation of patterns in subaqueous sediment - Kidanemariam, Aman Ghebremichael (Dissertationsreihe am Institut für Hydromechanik, Karlsruher Institut für Technologie / Karlsruher Institut für Technologie (KIT), Institut für Hydromechanik, 2016)
This book investigates the formation of subaqueous patterns by means of high-fidelity numerical simulations which resolve all the relevant scales of the flow and the sediment bed. This is required to provide a space- and time-resolved information on the flow field and the sediment bed. Secondly, detailed analysis of the generated data allows to address the different governing mechanisms involved in the formation of patterns as well as to access the validity of various existing models.